Immunology Survey on the Incidence of Infectious Bronchitis(IB) and Infectious Laryngotracheitis (ILT) in Poultry in and around Trichur - George M C (Department of Microbiology, College of Veterinary and Animal Sciences, 1979)
Infectious bronchitis and infectious laryngotrancheitis are the two viral diseases of poultry responsible for economic loss to the poultry industry by way of decreased egg production, poor quality of eggs, decreased feed efficiency and loss of weight gain. These disease have been reported from the neighbouring states of Kerala. In the present study a serological survey was carried out to understand the prevalence of these two disease in the poultry population in and around Trichur.